Comparison of Media and Methods for the Detection and Enumeration of Clostridium perfringens in Seafoods - LALITHA, K. V.; IYER, H. KRISHNA; IYER, K. MAHADEVA (Fishery Technology, 2017)
Three direct plating methods and two most probable number (MPN) procedures were compared for the enumeration of Clostridium perfringens in seafoods: the sulfitecycloserine (SC) agar, sulfite-polymyxin-sulfadiazine (SPS) agar, tryptone-sulfite- neomycin (TSN) agar, LS medium MPN procedure and iron milk MPN procedure. Isolates were confirmed as C. perfringens. The two MPN procedures compared very well with the three plating media tested with stock culture of C. perfringens from our laboratory collection and the reference strain NCIB 6125. But in fish samples, the two liquid media were found to be more sensitive and hence the MPN procedure using LS medium for the detection of C. perfringens in seafoods is suggested.